Writing About Oneself the Self-portrait: Archaeologist of Oneself - Bonilla, María (2014)
This article reports on the theatre, danse, photographie and poetry work of María Bonilla and Ana Muñoz during the last 20 years, and cover aspects of the theoretical issues from archeologie, litterature, self portrait and self-image.